Study on the Adsorption Behaviors of Metal Ions and the Floatability of the Silicate Minerals - Jia Muxin (International Mineral Processing Congress, 2003)
The adsorption behaviors of metal ions on a silicate mineral and the flotability of a metalized silicate mineral with sodium oleate as collector are closely related to the structure of the silicate mineral. The adsorption isothermals of the metal ions on different silicate minerals are studied, the parameters of the isothermal give the information how many surface oxygen anions a metal ions is attached to, from this information and the structure of the mineral the site where a metal ion is attached can be guessed (The adsorption isothermals and adsorption behaviors with pH are fitted with Temkin, Frenudlich and Kurbatov equations respectively). Metal ions as Cu2+, Ni2+, Zn2+ are attached to the oxygen anions of surface species –Si-O– on the quartz surface, most of them coordinate to only one surface oxygen, their adsorption ability on quartz is low, but this metal ions on quartz surface protrude out of the surface perfectly, so their ability to combine with oleate acid radical is excellent. Quartz can be activated well by such metal ions. The isothermal of Fe3+ on quartz indicates these cations coordinates with more than two surface oxygen anions. This means the Fe3+ nucleates on quartz surface in the form of Fe(OH)3 colloid particles. The isothermals of Cu2+, Ni2+, Zn2+ Fe3+ on spodumene shows such ions coordinate with more than two surface oxygen anions, it indicate these ions may attach to the position where Li+ is formerly exists, such metal ions stay in a cave on the mineral surface, their adsorption abilities on spodumene are quite well, but they are affect by the oxygen anions of the two Si tetrahedron chains, the can almost not activate this mineral. These cations may attach on the site where Al3+ exists on the muscovite surface, just like spodumene, muscovite can not be activated well by such cations. Pt2+ has a large ion radius, as Pauling’s rules depicts polyhedron can not attach to Si tetrahedron well, the adsorption ability of Pt2+ on quartz is low and quartz is activated badly by Pt2+. On the other Pt2+ can adsorb well on spodumene and muscovite well and activated them well because it is not affected so bad by the tetrahedron oxygen anions of the minerals for their its large radius. The isothermal of Ca2+ on quartz indicates a Ca2+ coordinates with less than one surface oxygen anion, this means Ca2+ attaches on quartz mainly by physical adsorption. The adsorption abilities on mineral surface and the interaction abilities with oleate acid radical of the transition metal ions with the same valence are guessed to be determined by their d electron number, the rules should be d1<d2<d3<d4>d5<d6<d7<d8<d9>d10. Hydrogen bond may play an important rule in the activation of the mineral by HF and the interaction of the HF activated silicate mineral with collectors. The general rule is high bond valence and small metal ion radius surface species –Me-O can be activated well by HF with sodium oleate as collector. For example – SiIV-OH is neutral while –SiIV-FH+ and –SiVI-FH+0.33 are positively charged, the positively charged surface species are more likely to connect oleate acid radical via hydrogen bonds.